2012
DOI: 10.1160/th12-05-0310
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomics of patients with non-valvular atrial fibrillation on chronic anti-coagulation with warfarin or a direct factor Xa inhibitor

Abstract: Plasma proteins mediate thrombogenesis, inflammation, endocardial injury and structural remodelling in atrial fibrillation (AF). We hypothesised that anti-coagulation with rivaroxaban, a direct factor Xa inhibitor, would differentially modulate biologically-relevant plasma proteins, compared with warfarin, a multi-coagulation protein antagonist. We performed unbiased liquid chromatography/tandem mass spectroscopy and candidate multiplexed protein immunoassays among Japanese subjects with non-valvular chronic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
6
23
1
Order By: Relevance
“…Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21). In the current study, we could confirm the previously observed associations between plasma fibulin-1 and age, glycemic status, and pulse pressure, although the correlations were not as strong as previously reported (18).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21). In the current study, we could confirm the previously observed associations between plasma fibulin-1 and age, glycemic status, and pulse pressure, although the correlations were not as strong as previously reported (18).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, plasma fibulin-1 concentrations independently predicted mortality in a 15-year follow-up period (18). Thus, plasma fibulin-1 appears as a new biomarker for vascular damage, which is in line with the results from four subsequent studies, where plasma fibulin-1 was found to be associated with diabetes, hypertension, and kidney damage (19)(20)(21). Interestingly, two of these studies used non-hypothesisdriven proteomic approaches to search for new markers (20,21).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…11 Because thrombin activates protein C when it binds thrombomodulin, 12 we preferred to preserve this natural anticoagulant mechanism and administered the direct inhibitor of activated factor X rivaroxaban, which also increases thrombomodulin plasma levels, to our patient. 13 Why does this child require such a high daily dose of rivaroxaban to be free from skin necrosis? The pharmacokinetic profile performed with a daily dose of 30 mg showed a rapid metabolism of the drug, particularly during the day, with a peak of activity reached 1 to 2 hours after oral intake and a mean half-life of 3.5 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced arterial barorefl ex sensitivity was reported in patients suffering from vasovagal syncope in some studies (1,3,4), whereas another studies did not found differences in barorefl ex sensitivity in these subjects (5). In some reports, an increased baroreceptor refl ex gain was observed in fainting subjects (6, 7).…”
Section: Introductionmentioning
confidence: 98%